Identification of cross-reactive epitope regions of bovine viral diarrhea virus and classical swine fever virus glycoproteins - Burton, Mollie K. (Kansas State University, 2016)
Pestiviruses such as classical swine fever virus (CSFV) and bovine viral diarrhea virus (BVDV) are some of the most economically important livestock diseases in the world. The antigenic similarities between members of the pestivirus genus allow for both BVDV and CSFV to infect swine. Infections with heterologous pestiviruses in swine can interfere with diagnostic tests for CSFV. The identification of cross-reactive and cross-neutralizing epitopes between CSFV and BVDV for the development of improved diagnostics and vaccines that allow for the differentiation of infected animals from vaccinated animals (DIVAs) are necessary to accurately detect and control CSFV. The overall goal of this research was to identify epitope regions recognized by antibodies that can differentiate between CSFV and BVDV. The approach was to use serum neutralization assays to confirm the presence of neutralizing antibodies to BVDV in swine serum collected from animals immunized with one of three separate Alphavirus vaccine constructs: BVDV-1b, CSFV E2, and CSFV E[superscript]rns. Results showed that animals immunized with the Alphavirus BVDV-1b construct had high neutralizing titers against BVDV-1a and animals immunized with Alphavirus CSFV E2 and E[superscript]rns constructs had low, but detectable, neutralizing activity. Polypeptide fragments of CSFV and BVDV E2 were then expressed in E. coli and purified using affinity chromatography. Serum from a pig immunized with the CSFV E2 Alphavirus construct was tested against two fragments of CSFV E2, 2/4 and 4/4, and four fragments BVDV E2, 1/4, 2/4, 3/4, and 4/4, using western blot analysis. Reactivity to fragments CSFV E2 2/4 and 4/4 and BVDV E2 1/4 and 4/4 was observed. The results of this study identified CSFV amino acid positions 774 through 857 and BVDV amino acid positions 783 through 872 as the regions that contain the epitopes recognized by cross-reactive antibodies between BVDV and CSFV E2. These results provide more specific sequence regions to improve CSFV diagnostic assays and DIVA vaccines.
Keywords: Immunology; Pestivirus; Epitope Mapping; Animal Diseases; Classical Swine Fever Virus; Bovine Viral Diarrhea Virus